Pineapple Collector Management Information System With Agile Model - Laila Fadillah, Cika; Fahry Maulana, Muhammad; Aulia Megi, Tria; Vernanda, Dwi; Azhariyah, Sari; Herdiawan, Tri; Piarna, Rian (Yayasan Insan Mulia Bima, 2025)
Pineapple collectors play an important role in the distribution of pineapples from farmers to buyers, but manual recording is still a major obstacle, causing inefficiency, difficult data access, and the risk of recording errors. This study aims to develop a technology-based pineapple collector management information system to improve recording efficiency, data accuracy, and smooth distribution. The research method uses an Agile approach, which involves the stages of planning, needs analysis, system design, development, testing, and implementation, with active participation of end users in each stage. The results of the study show that the developed system is able to improve recording efficiency, reduce errors, and speed up transactions and distribution. Key features include order tracking, payment recording, and stock management. In conclusion, this information system is an effective solution to overcome the problem of manual recording, increase operational efficiency, data transparency, and improve the relationship between farmers and buyers.